Nitrate and ammonium ions removal from groundwater by a hybrid system of zero-valent iron combined with adsorbents - Ji, Min-Kyu; Park, Won-Bae; Khan, Moonis Ali; Abou-Shanab, Reda A. I.; Kim, Yongje; Cho, Yunchul; Choi, Jaeyoung; Song, Hocheol; Jeon, Byong-Hun (ROYAL SOC CHEMISTRY, 2012)
Nitrate (NO3-) is a commonly found contaminant in groundwater and surface water. It has created a major water quality problem worldwide. The laboratory batch experiments were conducted to investigate the feasibility of HCl-treated zero-valent iron (Fe-0) combined with different adsorbents as hybrid systems for simultaneous removal of nitrate (NO3-) and ammonium (NH4+) ions from aqueous solution. The maximum NO3- removal in combined Fe-0-granular activated carbon (GAC), Fe-0-filtralite and Fe-0-sepiolite systems was 86, 96 and 99%, respectively, at 45 degrees C for 24 h reaction time. The NO3- removal rate increased with the increase in initial NO3- concentration. The NO3- removal efficiency by hybrid systems was in the order of sepiolite > filtralite > GAC. The NH4+ produced during the denitrification process by Fe-0 was successfully removed by the adsorbents, with the removal efficiency in the order of GAC > sepiolite > filtralite. Results of the present study suggest that the use of a hybrid system could be a promising technology for achieving simultaneous removal of NO3- and NH4+ ions from aqueous solution.
Keywords: GREEN RUST; REDUCTION; ADSORPTION; WATER; TRANSPORT; SEPIOLITE; PRODUCTS; KINETICS; NITROGEN; DYES